2019
DOI: 10.3892/or.2019.7425
|View full text |Cite
|
Sign up to set email alerts
|

Ruscogenin induces ferroptosis in pancreatic cancer cells

Abstract: Pancreatic cancer is characterized by aggressive and highly metastatic phenotypes. This disease exhibits a poor patient prognosis and is considered a challenge due to the limited treatment options encountered in clinical practice. Previous studies have shown that ruscogenin, a saponin found in the root of Ophiopogon japonicus, exerts a wide range of biological functions including anticancer activity. In the present study, the effects of ruscogenin were investigated on pancreatic cancer cells and the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…ARF6 can mitigate gemcitabine resistance by conferring PCa cells the sensitivity to RSL3-induced ferroptosis [ 34 ]. Studies have demonstrated that multiple chemical extracts can promote the death of pancreatic cancer cells mainly through the induction of ferroptosis [ 17 , 35 , 36 ]. Ferroptosis induced by SLC7A11 deletion has be verified to slow down the growth of the xenograft derived from PCa [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…ARF6 can mitigate gemcitabine resistance by conferring PCa cells the sensitivity to RSL3-induced ferroptosis [ 34 ]. Studies have demonstrated that multiple chemical extracts can promote the death of pancreatic cancer cells mainly through the induction of ferroptosis [ 17 , 35 , 36 ]. Ferroptosis induced by SLC7A11 deletion has be verified to slow down the growth of the xenograft derived from PCa [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many extracts from plants and herbs also exhibit anti-tumor effects by inducing ferroptosis. Ruscogenin can induce ferroptosis by improving ROS generation and trigger intracellular iron accumulation by upregulating transferrin and downregulating FPN ( 49 ). Piperlongumine can also induce ferroptosis in pancreatic cancer cells ( 171 ).…”
Section: Ferroptosis and Cancermentioning
confidence: 99%
“…Moreover, the combination of ART and GRP78 inhibitor worked in KRAS mutant PDAC ( Wang et al, 2019 ). Ruscogenin can also induce ferroptosis by influencing the levels of ferroportin and transferrin to exhibit anticancer effects ( Song et al, 2020 ). Yamaguchi et al (2018) demonstrated triple combined treatment using Cotylenin A, Piperlongumine, and sulfasalazine as a successful therapeutic method against PDAC.…”
Section: Ferroptosis In Relevant Malignant Tumorsmentioning
confidence: 99%
“…Moreover, it is time- and dose-dependent. Furthermore, in BxPC-3 human pancreatic cancer xenografts, there are significant antitumor effects without any toxicity detected in normal tissues ( Song et al, 2020 ).…”
Section: Ferroptosis-associated Anti-cancer Drugs In Preclinical Expementioning
confidence: 99%